2019
DOI: 10.1166/jnn.2019.16128
|View full text |Cite
|
Sign up to set email alerts
|

Sound Absorption and Insulation Properties of a Polyurethane Foam Mixed with Electrospun Nylon-6 and Polyurethane Nanofibre Mats

Abstract: In recent years, noise has become a serious hazard and can have permanent biological and psychological effects on humans and other organisms in nature. Textile materials are commonly used as absorbent acoustic materials for noise reduction. This work examines the use of electrospun nylon-6 and polyurethane nanofibres (PU NFs) to improve the sound absorption and sound insulation properties of polyurethane foam. In this work, nylon-6 and polyurethane nanofibres were prepared by an electrospinning techni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(18 citation statements)
references
References 0 publications
0
18
0
Order By: Relevance
“…Widely used for sound absorption [1][2][3], furniture [3,4], and insulating materials [5], polyurethane foam (PUF) plays an important role in our daily life. Compared with other insulating materials, PUF has the advantage of low thermal conductivity, high mechanical and chemical stability at both high and low temperatures, and the ability to form sandwich structures with various facer materials [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Widely used for sound absorption [1][2][3], furniture [3,4], and insulating materials [5], polyurethane foam (PUF) plays an important role in our daily life. Compared with other insulating materials, PUF has the advantage of low thermal conductivity, high mechanical and chemical stability at both high and low temperatures, and the ability to form sandwich structures with various facer materials [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…The main thermal events of pristine PU and PU‐composites were seen in the DTG graph (Figure 4(b)), which corresponded to the maximum degradation temperatures ( T max ). The pristine PU obtained three pronounced thermal events (between 250 and 400°C), where degradation started at T max 1 = 292.6°C, 72 followed by two more events ( T max 2 = 326.1°C and T max 3 = 354.4°C, regarding the urethane and polyol degradation, respectively). As for the composite foams, the urethane group degradation as a first event was delayed due to the addition of AR to higher temperatures.…”
Section: Resultsmentioning
confidence: 99%
“…Good elasticity of materials may promote the consumption of acoustic energy by the resonance effect, thus improving the sound absorption performance of the materials. Park et al [ 35 ] prepared polyurethane (PU) and nylon 6 composite nanofibers by electrospinning and then laminated them with polyurethane foam. They found that PU composite nanofibers perform better in sound absorption than nylon 6 composite nanofibers.…”
Section: Factors Influencing Sound Absorption Performance Of Electros...mentioning
confidence: 99%